A new microstrip patch antenna with triple‐polarization diversity. Issue 6 (June 2014) - Dasari, Rama Krishna; Pandharipande, V. M.; Koul, Shiban K.
ABSTRACT In recent years, polarization agility in single antenna is most desired characteristic in different applications. In this article, a microstrip antenna with new triple‐polarization diversity is designed and developed for C‐band pulsed altimeter used in many of the missile/aerospace application. The achieved polarization includes elliptical polarization, circular polarization (CP), and linear polarization. The antenna can be biased to get either right‐handed circular polarization (RHCP) or left‐handed circular polarization (LHCP). The antenna consists of a rectangular patch, four PIN diodes and two feeding lines along vertical and horizontal edge of the antenna. The necessary biasing network also embedded in the antenna circuit. Four PIN diodes are used for the polarization diversification and controlled by +5V external DC power supply. A prototype of the antenna has been fabricated and tested. Simulated results are in agreement with experimental data. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1348–1353, 2014